ON THE GIRTH, INDEPENDENCE NUMBER, AND WIENER INDEX OF COPRIME GRAPH OF DIHEDRAL GROUP - Agista Surya Bawana; Aluysius Sutjijana; Yeni Susanti (Barekeng)
The coprime graph of a finite group , denoted by , is a graph with vertex set  such that two distinct vertices  and  are adjacent if and only if their orders are coprime, i.e.,  where |x| is the order of x. In this paper, we complete the form of the coprime graph of a dihedral group that was given by previous research and it has been proved that  if , for some  and  if . Moreover, we prove that if  is even, then the independence number of  is , where  is the greatest odd divisor of  and if  is odd, then the independence number of  is . Furthermore, the Wiener index of coprime graph of dihedral group has been stated here.